2006
DOI: 10.1007/s10529-006-9044-4
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes in Bast Fibrous Plant Processing

Abstract: The program COST Action 847 Textile Quality and Biotechnology (2000-2005) has given an excellent chance to review the possibilities of the research, aiming at development of the industrial application of enzymes for bast fibrous plant degumming and primary processing. The recent advancements in enzymatic processing of bast fibrous plants (flax, hemp, jute, ramie and alike plants) and related textiles are given. The performance of enzymes in degumming, modification of bast fibres, roving, yarn, related fabrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 13 publications
0
34
0
1
Order By: Relevance
“…Significant activity levels were observed with the procedures of Bergmeyer and Bernt [17] which measures glucose and consequently glucoamylase activity (220 lmol/min) and also by Fuwa [18] procedure, appropriate for dextrinizing activity (a-amylase 310 lmol/ min) confirming the previous results. Avicelase and alkaline proteases appeared at low levels (70 lmol/min), nevertheless, other hydrolases, such as xylanase, pectinase, and acid and neutral proteases were detected in significant levels (963.3; 251.1; 1210 and 1935 lmol/min, respectively), further suggesting industrial applications of the fermentation procedure and the organism reported here [11,29,30].…”
Section: Hydrolysis Products Of the Amylase Activitymentioning
confidence: 56%
“…Significant activity levels were observed with the procedures of Bergmeyer and Bernt [17] which measures glucose and consequently glucoamylase activity (220 lmol/min) and also by Fuwa [18] procedure, appropriate for dextrinizing activity (a-amylase 310 lmol/ min) confirming the previous results. Avicelase and alkaline proteases appeared at low levels (70 lmol/min), nevertheless, other hydrolases, such as xylanase, pectinase, and acid and neutral proteases were detected in significant levels (963.3; 251.1; 1210 and 1935 lmol/min, respectively), further suggesting industrial applications of the fermentation procedure and the organism reported here [11,29,30].…”
Section: Hydrolysis Products Of the Amylase Activitymentioning
confidence: 56%
“…Addition of EDTA further to buffer and enzyme solution resulted in an increase in brightness and whiteness. Addition of EDTA facilitates the removal of water extractable impurities and calcium ions from the region that connect the macromolecule in pectin to one another or pectin to other polysaccharides [29]. Similarly, Csiszar et al reported that EDTA markedly enhanced the apparent activity of commercial xylanases and pectinases in cotton bioscouring, accelerating the degradation and removal of impurities [30].…”
Section: Resultsmentioning
confidence: 99%
“…followed by enzymatic, chemical or physical processing of fibres. [4][5][6][7][8][9][10][11] The scheme of the fibre plant degumming methods is shown in Figure 1.…”
Section: Fibre Extraction Methodsmentioning
confidence: 99%
“…An example of such methods is extraction of fibre by using the natural physical laws: water diffusion, osmosis and osmotic pressure [4][5][6][7][15][16][17][18][19]. All fibrous plants, especially flax and hemp, can undergo degumming process, where multiple water change or continuous water flow is used.…”
Section: Fibre Extraction Methodsmentioning
confidence: 99%